ANTI-INFLAMMATORY ACTIVITY OF ROTULA AQUATICA LOUR. IN ALBINO RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
The purpose of this study was to evaluate and compare the anti-inflammatory activity of different extracts of Rotula aquatica whole plant on acute inflammation (carrageenan-induced paw edema) and sub-acute inflammation (cotton pellet granuloma) in animal models. Five different groups of six animals each of either sex were used for acute and sub-acute experimental groups. Group I (control) received saline (5 ml/kg) and groups II rats were treated with indomethacin (10 mg/kg). Petroleum ether, ethyl acetate and ethanolic extracts of whole plant of Rotula aquatica at a dose of 200 mg/kg was given orally to group III, IV and V rats respectively. 1.0 ml of carrageenan was injected s.c. to plantar region of right hind paw of each rat, 1 hour after the drug administration. The change in paw volume was measured at 0, 1, 2 and 3 hours intervals. For sub-acute model of inflammation, sterilized cotton pellets, weighing 10 mg each, were implanted, one on each side of the groin, under light anaesthesia. Drug treatment was given for 7 days. On the eight day, cotton pellets along with granuloma were removed surgically, and wet pellets were weighed, after that dried at 60ºC overnight and then the dry pellets weight was taken. Petroleum ether and ethyl extracts at a dose of 200 mg/kg body weight exhibited significant inhibition (P<0.01) in acute and sub-acute inflammation models, which was comparable with standard drug (Indomethacin) whereas ethanolic extract showed marked inhibition (P<0.05). Rotula aquatica whole plant possesses anti-inflammatory effects in both acute and sub-acute inflammatory conditions and this may be possible to explain use of plant in traditional medicine.